PARASITIC FAUNA OF GASTROINTESTINAL TRACT OF DOMESTIC GOATS ON THE TERRITORY OF MOSCOW REGION - O. A. Panova; O. P. Kurnosova; I. M. Odoevskaya; A. V. Khrustalev; N. Y. Sysoeva; V. V. Semenovykh (Российский паразитологический журнал, 2019)
The purpose of the research is to study the parasitic fauna of the gastrointestinal tract of domestic goats in the Moscow region with the approbation of a standard treatment for identified types of pathogens of nematodoses.Materials and methods. 56 adult domestic goats have been studied in the Moscow Region in the summer-autumn period. The content of animals is pasture-stall. 98 fecal samples were examined for the presence of gastrointestinal parasites by the flotation method with a solution of ammonium nitrate, formalin-ether precipitation, the Berman method (Zajac, Conboy, 2012). The treatment regimens was applied on 11 goats with detected eggs of the fam. Strongylidae in feces samples, 4 with Nematodirus spp., 6 goats with combined infection of fam. Strongylidae and Trichuris spp. Therapy was performed with fenbendazole at a dose of 10 mg/kg for 5 days. When the efficiency was low, fenbendazole was repeated at a dose of 20 mg/kg 5 days. After treatment, feces were examined after 10, 30 and 90 days.Results and discussion. Domestic goats in the Moscow region have the following infections: nematodes fam. Strongylidae with extensive infection (EI) 44.6%, nematode Trichuris spp., EI 10.7%, Nematodirus spp. EI 3.6%, coccidioses Eimeria spp., EI 26.8% and Giardia spp., EI 3.6%. No trematode eggs or cestodes were found. The therapy with fenbendazole at a dose of 10 mg/kg within 5 days showed the 100% efficiency at strongylatosis and nematodirosis. Such dose was ineffective when a goat was parasitized by Trichuris spp. When the fenbendazole dose was increased to 20 mg/kg within 5 days, 100 % efficiency was obtained. All goats remained free from nematodes on the 30th and 90th days after the therapy according the results of coprological studies. An autopsy of one goat showed no parasites after the treatment. Fenbendazole remains an effective medication in treating gastrointestinal nematodosis of the goat.